Challenges to professionalism: Social accountability and global environmental change. (2nd September 2015) - Pearson, David; Walpole, Sarah; Barna, Stefi
Abstract: This article explores the concept of professionalism as it relates to social change and social accountability, and expands on them in the light of global environmental changes. Professionalism in medicine includes concepts of altruism, service, professional knowledge, self-regulation and autonomy. Current dialogues around social accountability suggest that medical schools should re-orientate their strategy and desired education, research and service outcomes to the health needs of the communities they serve.This article addresses the following questions:  How do we reconcile ideas of medical professionalism with the demands of creating a more equal, just, sustainable and socially inclusive society?  What new challenges do or will we face in relation to environmental degradation, biodiversity loss, ecosystem health and climate change?  How can medical schools best teach social and environmental responsiveness within a framework of professionalism?  How do medical schools ensure that tomorrow's doctors possess the knowledge, skills and attitude to adapt to the challenges they will face in future roles?We offer ideas about why and how medical educators can change, recommendations to strengthen the teaching of professionalism and social accountability and suggestions about the contribution of an emerging concept, that of "environmental accountability".